2017
DOI: 10.1002/jcsm.12224
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of sarcopenia among hospitalized older patients: results from the Glisten study

Abstract: BackgroundNew evidence is emerging on the importance of lean body mass during periods of illness and recovery. The preservation of lean body mass during such periods of intense stress impacts both patient and treatment outcomes. However, data concerning the incidence of sarcopenia among older people during hospitalization are scarce. The objective of this study was to evaluate the development of sarcopenia in a sample of hospitalized older subjects.MethodsWe used data of 394 participants from the multicentre I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
136
2
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(148 citation statements)
references
References 40 publications
7
136
2
3
Order By: Relevance
“…We could not include a positive control group for hospitalized patients that show atrophy of skeletal muscles other than from aspiration pneumonia. A previous study reported the incidence of sarcopenia among hospitalized aged patients . Because the methods to evaluate the muscles were completely different, we could not compare the degree of muscle atrophy with the previous study or other diseases.…”
Section: Discussionmentioning
confidence: 83%
“…We could not include a positive control group for hospitalized patients that show atrophy of skeletal muscles other than from aspiration pneumonia. A previous study reported the incidence of sarcopenia among hospitalized aged patients . Because the methods to evaluate the muscles were completely different, we could not compare the degree of muscle atrophy with the previous study or other diseases.…”
Section: Discussionmentioning
confidence: 83%
“…The authors acknowledge that a wide range of techniques have previously been used to describe changes in body composition and muscle size in clinical populations . BIA, however, is necessary as an alternative to more stringent measures of body composition in MD where mobility is limited .…”
Section: Discussionmentioning
confidence: 99%
“…This is one among the many different definitions of sarcopenia that have been suggested; however, no international consensus has been arrived at in this question. 19 Yang et al conducted a prospective observational study in acute care wards in teaching hospitals in Western China and obtained the survival status and readmission information after 12, 24, and 36 months after the baseline investigation. Whilst the total sample included 719 participants, incidence data were available for 302 participants with an incidence rate for sarcopenia of 3.7 cases per 100 personyears at risk.…”
Section: Prevalence and Incidence Of Sarcopenia In Elderly Populationsmentioning
confidence: 99%